Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan di Pabrik Gula Meritjan Kediri - Ahmad Samsuri; Mahfudiyanto Mahfudiyanto (BIMA : Journal of Business and Innovation Management, 2020)
This study aims to find out the Effect of Leadership Style and Work Discipline toward Employee Performance at Meritjan Sugar Factory in Kediri . This study uses quantitative with associative analysis. The sampling technique used was simple random sampling technique with 95 employees of the Meritjan sugar factory. The data collection techniques used were questionnaires, interviews, documentation and observation. In analyzing data using statistical methods, this study uses validity and reliability tests, classical assumption tests, and hypothesis testing with multiple linear regression formulas. The results of the study show that, (1) Leadership Style Does Not Affect Employee Performance at Meritjan Sugar Factory. (2) Work Discipline Significantly Affects Employee Performance at Meritjan Sugar Factory. (3) Work Leadership and Discipline Style Simultaneously Affect Employee Performance at Meritjan Sugar Factory